1987
DOI: 10.1139/v87-261
|View full text |Cite
|
Sign up to set email alerts
|

Crystal chemistry of complex indium(III) and other M(III) halides, with a discussion of M—Cl bond lengths in complex M(III) chlorides and of the structures of and hydrogen bonding in (NH4)2[InCl5(H2O)], K3InCl6nH2O, (MeNH3)4[InCl6]Cl, and (Me2NH2)4[InCl6]Cl

Abstract: . 1527 (1987). 65,The crystal chemistry of complex In(II1) halides is discussed and compared with that of other Group 111 elements and Fe(III), with critical comments and analysis of the available information. The cation/anion packing types occurring among A+ [M3+X4] halides are classified according to volume per formula unit and the relative ionic sizes of M, X, and A, and the structural trends in this class of compounds are identified. The effect of systematic factors responsible for variation in M(II1)-C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…There is a hydrogen-bonded arrangement of two independent (CH 3 NH 3 ) + cations, two independent octahedral (MX 6 ) À anions centered at Wyckoff positions a (0,0,0; 1 2 , 0, 1 2 ) and d (0, 0, 1 2 ; 1 2 , 0, 0), and two independent Cl À anions at Wyckoff positions e ( 3 4 , y, 3 4 ; 1 4 , Ày, 1 4 ) and f ( 3 4 , y, 1 4 ; 1 4 , Ày, 3 4 ) on twofold axes. This arrangement was ®rst described in detail by Knop et al (1987) for (CH 3 NH 3 ) 4 InCl 7 , the structure of which had been determined earlier by Schlimper & Ziegler (1972).…”
Section: The (Ch 3 Nhmentioning
confidence: 89%
See 1 more Smart Citation
“…There is a hydrogen-bonded arrangement of two independent (CH 3 NH 3 ) + cations, two independent octahedral (MX 6 ) À anions centered at Wyckoff positions a (0,0,0; 1 2 , 0, 1 2 ) and d (0, 0, 1 2 ; 1 2 , 0, 0), and two independent Cl À anions at Wyckoff positions e ( 3 4 , y, 3 4 ; 1 4 , Ày, 1 4 ) and f ( 3 4 , y, 1 4 ; 1 4 , Ày, 3 4 ) on twofold axes. This arrangement was ®rst described in detail by Knop et al (1987) for (CH 3 NH 3 ) 4 InCl 7 , the structure of which had been determined earlier by Schlimper & Ziegler (1972).…”
Section: The (Ch 3 Nhmentioning
confidence: 89%
“…The ®rst four compounds all crystallize in space group P2/n with Z = 4. FOXTIV10 was reported as monoclinic, Z = 2, space group P2, but can be transformed to the pseudo cell given in the Knop et al (1987); (2) James et al (1996); (3) Halepoto et al (1995). These authors do not mention the earlier work in references (1), (4) or (5); (4) Khan & Tuck (1981);(5) Czjzek et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…Thec orresponding X-ray diffraction (XRD) patterns were not matched to any particular chemicals including LiCl, InCl 3 ,InCl 3 •x H 2 O, and Li 3 InCl 6 .The obtained product was probably ah ydrated form of lithium indium chloride as Li 3 InCl 6 •x H 2 Os imilar to other indium halide hydrates,s uch as Cs 2 InBr 5 •H 2 O, [14] (NH 4 ) 2 InCl 5 •H 2 O [15] and K 3 InCl 6 •n H 2 O. [15] Coordinating water was confirmed by Fourier transform infrared spectroscopy (Figure S2). The number of coordinated water (x in Li 3 InCl 6 •x H 2 O) was estimated to be 2b yt hermogravimetric analysis (TGA, Figure S3).…”
mentioning
confidence: 98%
“…We calculated the lowest decomposition energies (∆H d ) of perovskites that have been reported, as shown in Table S2. According to the results, we concluded that double perovskites could been synthesized when ∆H d is greater than 0 meV per atom, [32,37,40,[52][53][54][55][56][57][58][59] and there is no synthesis in the experiment when ∆H d is lower than −29 meV per atom. It is worth noting that ∆H d is between −29-0 meV per atom, that is, Cs 2 AgSbCl 6 [44,60], Rb 2 NaInCl 6 [53], Cs 2 AgSbBr 6 [44], Cs 2 NaInBr 6 [53], Cs 2 KBiCl 6 [61], Cs 2 NaSbBr 6 [54], Cs 2 NaBiI 6 [43] and Cs 2 AgBiI 6 [62] are experimentally synthesized by synthesizing nanocrystals or controlling the experimental temperature.…”
Section: Linear Programming (Lp) For Thermodynamic Stabilitymentioning
confidence: 91%